Chapter 8 Felles mentale modeller i elitelagballspill - Giske, Rune (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The purpose of this inquiry is to explore team member knowledge among elite players in team ballgames - theoretically anchored in shared mental models. Team member knowledge is team specific and not a type of knowledge that players can transport from team to team. Current research literature has only to a limited extent been concerned about team member knowledge and the importance of this in team ball games. The following research questions will therefore be addressed in the present study: How do elite players describe their knowledge of co-players? How do players experience the knowledge development of co-players? The inquiry follows an ideographic research design, and the empirical material consists of interviews with four elite players in football and team handball. The analysis reveals that the following themes elaborate team member knowledge: Strengths and weaknesses, preferences and predictions, compensatory behavior and co-players' value. The players' experience of the development of team member knowledge indicates primarily implicit learning trajectories. The findings from the present study support the idea that team member knowledge is an important feature in handball and soccer elite teams. Coaches and players should therefore reflect on how this knowledge should be promoted."